Menggali Pemahaman Pelajar Tentang Korupsi - Damayanti, Ratnaningsih; Rahman, Fathur; Haboddin, Muhtar (Gorontalo Journal of Government and Political Studies, 2018)
ABSTRACTUnderstanding of corruption is not only task for KPK, government officials, and members of Parliament. Public also needs to understand corruption as part of anti-corruption education. Students are one of the elements of society who need to gain an understanding of anti-corruption or integrity because of their early age. Research conducted by survey to students in Malang in certain limits managed to reveal students' understanding about corruption. This research presents an understanding of theoretical corruption and then looks at the extent to which respondents understand about corruption. Student's understanding and knowledge about corruption, corruption behavior, corruption-related actors to what was the most popular corruption case. In addition, the students also know about the institution authorized in conducting the act of corruption. However, for the respondents, the best institution in working to eradicate corruption is KPK. The results of this study also show that students 'understanding of corruption in Indonesia is related to students' obedience to school rules. The more students understand about corruption, the more obedient they are to school rules. ABSTRAKSIMemahami korupsi bukan hanya tugas KPK, pegawai pemerintah, dan anggota DPR. Masyarakat juga perlu memahami korupsi sebagai bagian dari pendidikan anti korupsi. Pelajar sebagai bagian dari masyarakat yang perlu memahami anti korupsi atau integritas sejak dini. Penelitian yang dilakukan melalui survey kepada pelajar di Kota Malang ini dalam batasan tertentu mampu mengungkalan persepsi pelajar mengenai korupsi. Pemahaman dan pengetahuan pelajar tentang korupsi, perilaku korupsi, dan aktor yang terjerat kasus korupsi yang paling populer. Bagi responden, institusi terbaik yang dapat memberantas korupsi adalah KPK. Hasil penelitian ini juga menunjukkan pemahaman pelajar terhadap koruspi di Indonesia berhubungan dengan kepatuhan pelajar terhadap peraturan sekola. Semakin pelajar memahami korupsi, semakin patuh mereka terhadap peraturan sekolah.